1979
DOI: 10.1002/bit.260210503
|View full text |Cite
|
Sign up to set email alerts
|

Reactor properties of a high‐speed bead mill for microbial cell rupture

Abstract: SummaryLaboratory and pilot-plant high-speed bead mills of 0.6 and S liter capacity and consisting of four and five impellers in series, respectively, were used to follow the batch and continuous disruption of bakers' yeast (Sac.c.liurom?c.e.t ccwr,i.sicrc~). The mills are not scaled equivalents. Throughputs ranging from I x m3/sec to 12 x mYsec to 100 x 10P m3/sec for the 5 liter mill were used for continuous disruption studies. Variables studied included the effect of impeller tip speed, temperature, and pac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
31
0

Year Published

1993
1993
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(43 citation statements)
references
References 15 publications
12
31
0
Order By: Relevance
“…This is contrary to Hetherington et al [16] , who reported that maximum amount of protein release is independent of pressure. However, the result of this study is similar to that reported by Limon-Lason et al [17] , who explained that it was due to the release of insoluble protein complex and peptides through micronization of cell debris at higher pressure. Cell disruption is a two step processes which involved point break of cell envelope and followed by disintegration of cell wall along with degradation of cell debris [3] .…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This is contrary to Hetherington et al [16] , who reported that maximum amount of protein release is independent of pressure. However, the result of this study is similar to that reported by Limon-Lason et al [17] , who explained that it was due to the release of insoluble protein complex and peptides through micronization of cell debris at higher pressure. Cell disruption is a two step processes which involved point break of cell envelope and followed by disintegration of cell wall along with degradation of cell debris [3] .…”
Section: Discussionsupporting
confidence: 91%
“…At 1600 bar, Van Hee et al [20] observed an increase of IB with increasing number of passes for the disruption of Pseudomonas Putida without any note of soluble protein content. IB is not the original content of soluble component and has increased due to the micronization of cell debris which was in agreement with Limon-Lason et al [17] . So this pressure range can be classified as high pressure range where the maximum protein release and lower particle size can be achieved after the first pass of homogenization.…”
Section: Discussionsupporting
confidence: 90%
“…For pDNA(sc), the significant treatments were mill frequency, bead size, and the combination of the three parameters studied in this research. Although ANOVA for RSM demonstrated that cellular concentration per se is not a significant parameter in this operation, as it was also concluded by other authors in the disruption of E. coli cells [40] and yeast cells [20], it was found in this work that it is a crucial parameter for effective cell lysis. Since the best results of the release of pDNA(sc) were obtained with a small bead size and low cell concentrations, in order to optimize the disruption of E. coli for the release of pDNA(sc), we also suggest the use of a denser material with higher specific gravity than glass, e.g., zirconium beads, as reported by Haque et al [18], to increase cellular concentration and productivity.…”
Section: Discussionsupporting
confidence: 47%
“…Bead milling is one of the most preferable mechanical cell lysis methods at the industrial scale due to its ease of operation, controllability, and ability to load concentrated cell slurry [17,19]. This method has been a subject of continuing research in batch and continuous modes [19,20]. The common principle of a bead mill is that the cells are subjected to high stress produced by abrasion during rapid agitation with glass beads, resulting in the breaking of the membrane and cell wall, releasing all intracellular components [21].…”
Section: Introductionmentioning
confidence: 99%
“…The rate constant for a laboratory machine, k , is proportional to agitator peripheral velocity, u p , with a constant of proportionality equal to 0.0036 m − 1 [15] . In continuous operation, the bead mill acts like a series of continuous stirred tank reactor s ( CSTR s), each undergoing a fi rst -order disruption " reaction. "…”
Section: Modelingmentioning
confidence: 99%